ANALYSIS OF JOB TRAINING AND COMPETENCE ON WORK PRODUCTIVITY WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE IN THE AGENCY FINANCE AND REGIONAL ASSETS OF NORTH SUMATRA PROVINCE - Muhammad Fahmi; Elfitra Desy Surya; Mesra B (RADJA PUBLIKA, 2024)
This study aims to analyze the effect of job training and competence on work productivity with work discipline as an intervening variable at the Regional Finance and Asset Agency of North Sumatra Province. This study uses a quantitative approach with a survey method by distributing questionnaires to 80 employees as respondents. The research sample was determined using a purposive sampling technique so that the data obtained is relevant to the focus of the study. The collected data were analyzed using path analysis to determine the direct and indirect effects between variables. The results of the study indicate that job training has a positive and significant effect on work productivity, but through work discipline it has a positive but insignificant effect. Competence has a positive and significant effect on work productivity, as well as through work discipline. Work discipline also has a positive and significant effect on work productivity. In addition, job training through work discipline has a positive but insignificant effect on work productivity, but competence through work discipline has a positive and significant effect on work productivity. Thus, work discipline acts as an intervening variable that mediates only for competence on work productivity. These findings are expected to be a consideration for leaders in increasing work productivity through the implementation of effective job training, increasing competence, and implementing good work discipline in the organizational environment.